2009
DOI: 10.1073/pnas.0712077106
|View full text |Cite|
|
Sign up to set email alerts
|

Defined tuberculosis vaccine, Mtb72F/AS02A, evidence of protection in cynomolgus monkeys

Abstract: The development of a vaccine for tuberculosis requires a combination of antigens and adjuvants capable of inducing appropriate and long-lasting T cell immunity. We evaluated Mtb72F formulated in AS02A in the cynomolgus monkey model. The vaccine was immunogenic and caused no adverse reactions. When monkeys were immunized with bacillus Calmette–Guérin (BCG) and then boosted with Mtb72F in AS02A, protection superior to that afforded by using BCG alone was achieved, as measured by clinical parameters, pathology, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(107 citation statements)
references
References 21 publications
3
101
2
1
Order By: Relevance
“…The efficient containment of subclinical infection in the H56-boosted animals resulted in limited disease spread, and several animals had minimal disease and pathology at necropsy (Figure 4). This result is in contrast to findings from studies testing other vaccines in non-human primates, where substantial pathology was observed in boosted groups (37), in some cases at a higher level than in animals receiving only BCG (28). The finding that a vaccine (i.e., H56) can prevent reactivation of true latent infection is, to our knowledge, novel in the study of vaccines against TB and supports the hypothesis of a multi-stage vaccine generating long-term protection against disease.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The efficient containment of subclinical infection in the H56-boosted animals resulted in limited disease spread, and several animals had minimal disease and pathology at necropsy (Figure 4). This result is in contrast to findings from studies testing other vaccines in non-human primates, where substantial pathology was observed in boosted groups (37), in some cases at a higher level than in animals receiving only BCG (28). The finding that a vaccine (i.e., H56) can prevent reactivation of true latent infection is, to our knowledge, novel in the study of vaccines against TB and supports the hypothesis of a multi-stage vaccine generating long-term protection against disease.…”
Section: Discussioncontrasting
confidence: 55%
“…While a number of vaccine efficacy studies have been published using the high-dose cynomolgus or rhesus macaque models of infection (8,37,41,42), to our knowledge this is the first vaccine trial in which both low- and high-dose M. tuberculosis challenges were performed. The H56 booster vaccine gave similar outcomes in the two models, and in particular very low levels of the inflammation marker ESR and low infection-driven responses to CFP10 were striking observations in both experiments and indicated efficient control of bacterial replication.…”
Section: Figurementioning
confidence: 99%
“…Mtb72F, formulated with GSK Biologicals' proprietary AS02 A adjuvant system, was shown to be well tolerated in animal models and protected against M. tuberculosis challenge in nonhuman primates, where Mtb72F/ AS02 A was shown to be capable of inducing long-term protection against tuberculosis, as determined by protection against severe disease and death and by other clinical and histopathological parameters (6,30,34,39). A first-time-in-human study evaluated Mtb72F/AS02 A (10 g) in purified protein derivative (PPD)-negative TB-naïve, healthy adults in the United States given according to a 0-, 1-, and 2-month schedule and was found to be clinically well tolerated and highly immunogenic (42).…”
mentioning
confidence: 99%
“…In subsequent work, this antigen has been evaluated as part of the poly-protein subunit vaccine candidate, Mtb72f (Leroux-Roels et al, 2010;Reed et al, 2009). Collectively, all these results indicate that PE/PPE proteins are worthy of further evaluation as potentially protective antigens for inclusion in new TB vaccine candidates.…”
Section: Cell-mediated Immunity Conferred By Cd4+t Cells Is Critical mentioning
confidence: 99%